Cannabinoid therapeutics in orofacial pain management: a systematic review. (29th September 2022) - Votrubec, C; Tran, P; Lei, A; Brunet, Z; Bean, L; Olsen, BW; Sharma, D
Abstract: The objective of this paper was to investigate the published evidence regarding effects of cannabinoids (natural and synthetic) on post‐operative and/or out‐of‐office pain management in patients suffering from orofacial pain that presents in the dental setting. Three online databases (Ovid (MEDLINE), PubMed (MEDLINE), Scopus) were searched (July 2021). Additional studies were sought through grey literature searching (Cochrane Library Trials and ClinicalTrials.gov ) and hand‐searching the reference lists of included articles. All studies that analysed cannabinoid products and pain management of conditions that present in the general or specialist dental setting in the English language were included. Of the five articles included, one reported a significant effect on temporomandibular disorder pain relief using a topical cannabidiol formulation compared to a placebo. Four articles reported no significant effects of cannabinoids for pain management across various orofacial pain conditions. Although one study reported a positive effect, insufficient evidence exists to support a tangible clinical benefit of cannabinoids in managing orofacial pain, further research is recommended to investigate the benefits of cannabinoids' use. © 2022 Australian Dental Association.